International knowledge flows and technological advance: The role of migration - Kacey N. Douglas (IZA Journal of Migration, 2015)
This paper investigates whether knowledge flows from host to source country as a result of migration, alleviating the negative effects associated with outward migration. Using a fixed effects Poisson regression, patent citations are used as a proxy for knowledge flows and regressed on immigration and other control variables; the effect of immigration on patent citations is found to be positive and statistically significant. Additionally, the coefficient on immigration is found to be robust to different parameter changes in the model. These results suggest that reverse knowledge flows from outward migration help mitigate negative effects of outward migration on source countries.
Keywords: F22; O30; O15; 330; Immigration; Patent citations; Knowledge flows; Brain drain